Long-Term Survival, Posttraumatic Stress, and Quality of Life post Extracorporeal Membrane Oxygenation. Issue 8 (August 2020) - Harley, Olivia; Reynolds, Claire; Nair, Priya; Buscher, Hergen
Abstract : The past years has seen a surge in usage of extracorporeal membrane oxygenation (ECMO). Little is known about long-term survival, posttraumatic stress, and quality of life (QoL). A single-centre retrospective cohort study on consecutive patients supported with ECMO between 2012 and 2016. Survivors completed a QoL questionnaire (Short-Form 36 [SF-36]) and the posttraumatic stress disorder (PTSD) Civilian Version (PCL-C). Two-hundred forty-one patients (age 52 years, 158 males) received ECMO. One hundred fifty-one patients (62.7%) survived to discharge, of these 129 (85%) were alive at a median follow-up of 31.8 months. Median survival was 56.6 months. Seventy-six (58.9%) returned a completed survey. The ECMO cohort experienced a decrease in QoL in all domains which was significantly associated with a high risk for PTSD with 30.8% in the highest PTSD risk bracket. Renal replacement therapy and duration of ECMO were significantly associated with increased mortality but not with QoL. The diagnoses of primary graft dysfunction or respiratory failure were independently associated with better long-term survival, but there was no difference in QoL between different underlying conditions. Despite good long-term survival rates, reduced QoL and PTSD were frequently observed. These findings reaffirm the need for long-term follow-up and rehabilitation in this population. Abstract : Supplemental Digital Content is available in the text.